Mechanism of burning synthesis gas from coal - Messerle, V.E.; Ossadchaya, E.F.; Slavinskaya, N.A.; Ustimenko, A.B. (Recent Contributions to Physics, 2014)
The paper presents the scheme for producing synthesis gas by plasma gasification of solid fuels and detailed analysis of the existing literature on combustion synthesis gas (CO + H2). Analyzed and systematized the main known kinetic mechanisms of oxidation of synthesis gas. Chosen the experimental data used to test them and found the parameters of applicability of these mechanisms. Found and analyzed experimental data on ignition delay, flame spread rate and concentrations of components H2/CO/O2. For these data, the optimization of the kinetic parameters of the basic mechanism of oxidation reactions of synthesis gas. Modified values of reaction rate constants were thus in the interval error. The resulting kinetic mechanism of combustion synthesis gas is in good agreement with all approved to consider the source data.